2001
DOI: 10.1093/nar/29.17.3495
|View full text |Cite
|
Sign up to set email alerts
|

An enhancer element 6 kb upstream of the mouse HNF4alpha1 promoter is activated by glucocorticoids and liver-enriched transcription factors

Abstract: We have characterized a 700 bp enhancer element around -6 kb relative to the HNF4alpha1 transcription start. This element increases activity and confers glucocorticoid induction to a heterologous as well as the homologous promoters in differentiated hepatoma cells and is transactivated by HNF4alpha1, HNF4alpha7, HNF1alpha and HNF1beta in dedifferentiated hepatoma cells. A 240 bp sub-region conserves basal and hormone-induced enhancer activity. It contains HNF1, HNF4, HNF3 and C/EBP binding sites as shown by DN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
51
1
1

Year Published

2003
2003
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(54 citation statements)
references
References 59 publications
1
51
1
1
Order By: Relevance
“…Whether this effect exists at physiological concentrations of glucocorticoids remains unknown. However, the interaction of glucocorticoids and Hnf4a is further supported by the recent identification in mouse Hnf4a of an enhancer element containing a glucocorticoid response sequence [41]. These data are consistent with a mechanism in which prenatal glucocorticoid exposure alters hepatic Hnf4a isoforms with the ratio of P1-promoter-driven transcripts (Hnf4a1/2) 'fixed' at a permanently high level, which would lead to permanent overactivity of the target genes such as Pck2, and contribute to hyperglycaemia.…”
Section: Discussionsupporting
confidence: 65%
“…Whether this effect exists at physiological concentrations of glucocorticoids remains unknown. However, the interaction of glucocorticoids and Hnf4a is further supported by the recent identification in mouse Hnf4a of an enhancer element containing a glucocorticoid response sequence [41]. These data are consistent with a mechanism in which prenatal glucocorticoid exposure alters hepatic Hnf4a isoforms with the ratio of P1-promoter-driven transcripts (Hnf4a1/2) 'fixed' at a permanently high level, which would lead to permanent overactivity of the target genes such as Pck2, and contribute to hyperglycaemia.…”
Section: Discussionsupporting
confidence: 65%
“…This less open chromatin configuration at the enhancer could explain the lower levels of Hnf4a P2 transcripts in INS-1 cells compared with adult islets (60% less). In support of this hypothesis, we found that transfecting INS-1 cells with a construct containing the enhancer region (27) cloned upstream of the P2 promoter resulted in a 60% increase in luciferase activity compared with a vector containing only the P2 promoter, whereas the enhancer alone lacked any promoter activity (Fig. S3G).…”
Section: Dna Methylation and Histone Modifications Regulate Hnf4amentioning
confidence: 56%
“…It has been reported that HNF4␣ expression is self-regulated both directly and indirectly. HNF4␣ directly binds to the enhancer element of the HNF4␣ gene and stimulates its own expression (20). In addi- a Luciferase assays were performed using pMTP204-Luc as described under "Experimental Procedures".…”
Section: Identification Of Luteolin As a Food Compoundmentioning
confidence: 99%
“…tion, the transcription factors HNF1␣ and COUP-TFII are target genes of HNF4␣; HNF1␣ and COUP-TFII stimulate HNF4␣ gene expression (20,21). These observations led us to investigate whether the suppression of HNF4␣ activity by treatment with luteolin caused a decrease in the mRNA level of HNF4␣ itself in HepG2 cells.…”
Section: Identification Of Luteolin As a Food Compoundmentioning
confidence: 99%